Bibliothekserlaubnisse im Urheberrecht - Talke, Armin (Universitätsverlag der Technischen Universität Berlin, 2021)
The book deals in detail with the requirements of existing copyright exceptions, for libraries in German statutory copyright law. In Germany, the same as in all other EU member states, it is the rule that for copyright related "exploitations", such as copying, distribution, presentation or (internet-) communication to the public , there must exist a copyright exception or, if the conditions for such an exception are not met, the consent of the copyright holder must be provided. In 2018, especially for scientists, research and educational institutions, libraries and other cultural heritage institutions , new exceptions were created in §§ 60a ff. of the German Copyright Act (UrhG). At the time of publication of this version of the book, the next copyright reform is on its way, namely the implementation of the "Copyright in the Digital Single Market" Directive ("DSM Directive"). This publication refers to the provisions of the Directive from the respective passages. The DSM Directive must be implemented into German law by June 7, 2021.